UPAYA MENINGKATKAN KETERAMPILAN INTERPRETASI DATA DAN KOLABORASI PESERTA DIDIK MELALUI PENERAPAN MODEL DISCOVERY LEARNING KELAS X SMK NEGERI 1 BANTAN - Devni Gusliza Sari; Azizahwati Azizahwati; Zulirfan Zulirfan (Physics Education Study Program, Faculty of Education and Teacher Training, UNSIQ, 2025)
The mastery of students data interpretation and collaboration skills in schools is still relatively low, falling into the “fair” category. Therefore, strategies are needed to improve these skills. This study aims to improve students’ data interpretation skills and collaboration skills through the implementation of the discovery learning model. The research employed a Classroom Action Research (CAR) design conducted in two cycles. The subjects were 11 grade X ATPH students. Data were collected using a data interpretation skills test and a collaboration observation sheet, both of which had been content-validated by experts. The results showed that teacher activity increased from 82% in Cycle I to 88% in Cycle II, while student activity increased from 80% to 84%. The average student collaboration skills improved from 54% in the pre-cycle to 66% at the end of Cycle I, and further increased to 72% at the end of Cycle II, with all indicators falling into the collaborative category. Data interpretation skills also showed improvement, with the class average rising from 68% in Cycle I to 77% in Cycle II. These findings indicate that the implementation of the discovery learning model is effective in enhancing students’ data interpretation and collaboration skills. This model can serve as an alternative instructional strategy to foster the development of data interpretation and collaboration skills in the classroom.